BAMBOO FOUNDATION DENGAN PENDEKATAN SUSTAINABLE ARCHITECTURE DI BOYOLALI - Kusumo, Adi Surya; Pitana, Titis Srimuda; Suastika, Made (ARSITEKTURA, 2016)
The background of designing Bamboo Foundation in Boyolali is the emergence of human’s awareness to save the environment especially in the use of eco-friendly building materials. Unfortunately these phenomenon is used by several parties to gain much profit by producing materials and labeling their product with eco-friendly label and then sell them in a very expensive price. Because of the phenomenon then occur an idea to persuade the society to use eco-friendly materials but in a cheap price and good quality which is bamboo. Along  with the finding of bamboo preservation and processing methods ,it shows that bamboo has a big potential to be used as main material in a construction. So the existence of Bamboo Foundation to provide education about bamboo for the society. The designing problem is not only how to develop the bamboo preservatives and processing education but also about the conservation of various bamboo species based on the application of sustainable architecture in Bamboo Foundation design. The method used is architectural design method that combine various bamboo construction structure with the application of sustainability architecture. The result is the design of a bamboo education facilities consists of gallery, class, workshop, bamboo conservation, and supporting buildings that also use as a precedent for the visitors. Keywords: Bamboo, Conservation, Education, Sustainable Architecture.